A Single Codon Optimization Enhances Recombinant Human TNF-α Vaccine Expression in Escherichia coli. (15th April 2018) - Chu, Chu; Zhang, Wangqian; Li, Jialin; Wan, Yi; Wang, Zenglu; Duan, Ruyi; Yu, Pei; Zhao, Ning; Zhang, Kuo; Wang, Shuning; Hao, Qiang; Li, Weina; et al.
Abstract : As a proinflammatory cytokine, tumor necrosis factor-alpha (TNF- α ) plays a pivotal role in various autoimmune diseases such as rheumatoid arthritis (RA). Thus, TNF- α has been defined as a therapeutic target for RA. Although some TNF- α antagonists including neutralizing monoclonal antibodies and soluble receptors have been approved to be successful in attenuating symptoms in patients suffering from RA, the long-term use of these passive immunization reagents could cause some problems like a variable degree of immunogenicity. In the present study, in order to wake up active immune responses of RA patients, we developed a recombinant TNF- α therapeutic vaccine (named mrTNF-PADRE) by coupling a 12-amino acid universal Pan HLA-DR Epitope (PADRE) to the protein. Codon optimization was performed to improve the secondary structure of mrTNF-PADRE mRNA to ensure its heterologous expression. As a result, a single codon synonymous mutation greatly elevated recombinant protein expression (about 30% of the total bacteria proteins) in E. coli as compared with the undetectable expression of the unoptimized gene. Although expressed as insoluble inclusion bodies (IBs), the vaccine can be effectively prepared with a purity of over 95% by IBs washing and one-step gel-infiltration chromatography. By this strategy, a stable yield of 5.2 mg purified mrTNF-PADRE per gram of cell paste could be obtained.